2011
DOI: 10.1097/mpa.0b013e3182211bbf
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profile Changes and Importance of Low Serum α-Lipoprotein Fraction (High-Density Lipoprotein) in Cases With Acute Pancreatitis

Abstract: The low levels of HDL in AP cases during acute attack are associated with severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…When combined with lower lipoprotein lipase activity, this might lead to higher serum concentrations of triglycerides [25], a tendency observed in this study also. Bugdaci et al [26] have previously studied the lipid profile in patients with acute pancreatitis. They reported an association with low serum HDL cholesterol concentration and longer hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…When combined with lower lipoprotein lipase activity, this might lead to higher serum concentrations of triglycerides [25], a tendency observed in this study also. Bugdaci et al [26] have previously studied the lipid profile in patients with acute pancreatitis. They reported an association with low serum HDL cholesterol concentration and longer hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Bugdaci et al suggested two possible pathways. 40 First, they found that patients with acute pancreatitis had mild elevation of thyroid-stimulating hormone, possibly due to the systemic inflammatory state in acute pancreatitis. Transient elevation of thyroid-stimulating hormone could increase the level of triglycerides.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…9,37 Levels of high-density lipoprotein (HDL) during acute pancreatitis are low and directly associated with the severity of disease. 40 Elevation of triglycerides is associated with low HDL levels. The theory proposed is that the inflammatory state in acute pancreatitis increases triglyceride levels and suppresses HDL levels.…”
Section: Dyslipidemiamentioning
confidence: 99%
See 2 more Smart Citations